Laparoscopic Excision of Giant Mucinous Ovarian Borderline Tumor. Is A Safely Approach? - Bogliatto, Fabrizio; Crana, Francesco; Marino, Antonio Alessandro (Archives of Clinical and Medical Case Reports, 2020)
Cases of giant mucinous ovarian borderline tumors are rarely described in literature, with different clinical manifestations and difficult diagnostic assessment. In the present paper we report the case of a 60 years old woman with a giant mucinous borderline left ovarian tumor (>34 cm in maximum diameter) with 15.000 ml of free fluid inside. Laparotomic approach is usually preferred in these cases, but it exposes patients to higher rate of complications. We demonstrate that laparoscopy is safe and effective in managing large adnexal masses more than 30 cm in diameter.